Surface processing to improve the fatigue strength of bainitic steels – An overview - Luciano Dalcin, Rafael; Afonso Hatwig, Rodrigo; Fonseca Oliveira, Leonardo; Zottis, Juliana; da Silva Rocha, Alexandre; Epp, Jérémy; Zoch, Hans-Werner (International Journal of Engineering and Technology, 2019)
Currently, one of the major challenges for automotive industries is to reduce the weight and energy consumption of vehicles by using stronger and advanced low-cost materials. Conventional solutions using quenched and tempered steels not always fulfill the desired technical, economic and environmental requirements. Modern continuous cooling bainitic steels can provide a good combination of mechanical strength and toughness, being considered an excellent alternative to replace quenched and tempered martensitic steels in the manufacture of forged components. To meet the desired industry standards in highly loaded components, properties like surface hardness, fatigue strength, wear and friction resistance of these steels can be further improved by subsequent mechanical and thermochemical treatments. Therefore, this paper presents the state of the art in the use of continuous cooling bainitic steels for forging and low energy consumption surface improvement techniques such as: deep rolling and plasma nitriding. Finally, case studies are presented, and conclusions drawn on the current trends and reported practices. Surface modification techniques must be carefully controlled and combined with the material of interest to ensure that undesirable characteristics are not introduced during the manufacturing of the components. The development of processes based on the use of forged continuous cooling bainitic steels can be an excellent alternative to replace the conventional quenching and tempering treatment with considerable reduction of the energy consumption.Â